Neuronal Delamination and Outer Radial Glia Generation in Neocortical Development - Kawaguchi, Ayano (Frontiers in Cell and Developmental Biology, 2021)
During neocortical development, many neuronally differentiating cells (neurons and intermediate progenitor cells) are generated at the apical/ventricular surface by the division of neural progenitor cells (apical radial glial cells, aRG). Neurogenic cell delamination, in which these neuronally differentiating cells retract their apical processes and depart from the apical surface, is the first step of their migration. Since the microenvironment established by the apical endfeet is crucial for maintaining NE/aRGs, proper timing of the detachment of the apical endfeet is critical for the quantitative control of neurogenesis in cerebral development. During delamination, the microtubule-actin-AJ (adherens junction) configuration at the apical endfeet shows dynamic changes, concurrent with the constriction of the AJ ring at the apical endfeet and downregulation of cadherin expression. This process is mediated by transcriptional suppression of AJ-related molecules and multiple cascades to regulate cell adhesion and cytoskeletal architecture in a posttranscriptional manner. Recent advances have added molecules to the latter category: the interphase centrosome protein AKNA affects microtubule dynamics to destabilize the microtubule-actin-AJ complex, and the microtubule-associated protein Lzts1 inhibits microtubule assembly and activates actomyosin systems at the apical endfeet of differentiating cells. Moreover, Lzts1 induces the oblique division of aRGs, and loss of Lzts1 reduces the generation of outer radial glia (oRGs, also called basal radial glia, bRGs), another type of neural progenitor cell in the subventricular zone. These findings suggest that neurogenic cell delamination, and in some cases oRG generation, could be caused by a spectrum of interlinked mechanisms.